Pengaruh Guided Imagery Terhadap Frekuensi Napas Pada Pasien Asma Di Wilayah Kerja Puskesmas Paruga Kota Bima Tahun 2017 - Haris Haris; Julhana Julhana; Ulfa Nadira (Politeknik Kesehatan Kemenkes RI Jakarta I, 2018)
One of the psychological therapies that can be performed in patients with asthma is guided imagery. Guided imagery is a technique that uses the imagination of individuals with directional imagination to reduce stress. Frequency of breath is a process of inspiration and expiration in units of time / minute. When medical therapy is incapable of improving the patient's condition, alternative therapies such as guided imagery can be one of the interventions that nurses can provide. Objective : To analyze the influence of guided imagery therapy on respiratory rate in asthma patients In the Working Area of ​​Puskesmas Paruga Kota Bima. Methods : The design used in this study was pre-experimental with one group Pre-Post Test (one group pre-post test design). Sampling method using stratified random sampling with the number of samples of 30 respondents. The research instrument used is the observation sheet and watches. Data were analyzed using Paired T-Test with significant level (p = value ≤ 0,05). Results : The study showed a significant influence between guided imagery therapy on respiratory rate in asthma patients with p value = 0.05, H0 is rejected and Ha accepted or there is influence between guided imagery therapy on breath frequency in asthma patients. Conclusion : Based on the results of the study, the nurse needs to do guided imagery therapy in asthma patients. This is because guided imagery therapy can affect the frequency of breathing in asthma patients.